Prenatal findings and molecular cytogenetic analyses of a de novo interstitial deletion of 1q23.3 encompassing PBX1 gene - Manna Sun; Jiwu Lou; Qiaoyi Li; Jianhong Chen; Yujuan Li; Dongzhi Li; Haiming Yuan; Yanhui Liu (Elsevier, 2019)
Objectives: To present the prenatal findings and the molecular cytogenetic analyses of a de novo interstitial deletion of 1q23.3 encompassing PBX1 gene. Case report: A 32-year-old woman (gravida 1, para 0) underwent amniocentesis at 26 weeks' gestation because of constant small fetal kidneys on prenatal ultrasound. Chromosome microarray analysis (CMA) detected a de novo deletion of 1.871 Mb at 1q23.3. The deletion encompassed 2 genes of PBX1 and LMX1A. PBX1 haploinsufficiency had been reported to lead syndromic congenital anomalies of kidney and urinary tract (CAKUT) in humans. Furthermore, at 31 weeks' gestation, borderline oligohydramnios and restricted fetal dimensions were revealed. Ultimately, the pregnancy was terminated at 32 weeks with a 1500-g female fetus presenting polydactyl of left hand. Conclusions: The shared phenotypes between this case and the previously published prenatal cases demonstrate that loss of function mutation in PBX1 should be suspicious in fetus with bilateral renal hypoplasia, oligohydramnios and intrauterine growth retardation (IUGR). Keywords: PBX1, Renal hypoplasia, Prenatal diagnosis, Chromosome microarray analysis